GROWTH PATTERNS OF THE LOCOMOTOR LENGTH DIMENSIONS THE FEMALE BALI DUCKS - Suryawan, I Made Edi; Sampurna, I Putu; Suatha, I Ketut (Buletin Veteriner Udayana, 2017)
Study aims to determine the difference of time to reach the inflection point and the adult size. The measured of inflection point include  the length of the humerus, radius ulna, metatarsus, femur, tibia fibula, metacarpus, 1 st digiti, 2 nd digiti, 3 rd digiti, and 4 th digiti respectively.  The sample of this study were 70 female bali ducks, consist of 35 at the aged of 0 – 13 weeks, and the other 35 at the aged of 14 – 26 weeks. The data were analyzed by analysis of variance for time of reached the inflection point and the adult size, and by the regression analysis of the sigmoid pattern were used two parameters for newly hatched and reaching the maximum size. The results showed that the inflection point of metatarsus,  tibia fibula, metacarpal, 1 st digiti, 2 nd digiti  3 rd digiti, and  4 th digiti  length is less than a week, the length of  humerus and femur  were achieved at the age of one to two weeks, and the  metatarsal length were reached at the age of two to three weeks. The adult size of locomotor female bali ducks, starting from the length of the femur, followed by the radius ulna, humerus, tibia fibula, 4 th digiti, 3 rd digiti, 2 nd digiti, metacarpal, 1 st digiti and the last one is metatarsus. Study aims to determine the difference of time to reach the inflection point and the adult size. The measured of inflection point include  the length of the humerus, radius ulna, metatarsus, femur, tibia fibula, metacarpus, 1 st digiti, 2 nd digiti, 3 rd digiti, and 4 th digiti respectively.  The sample of this study were 70 female bali ducks, consist of 35 at the aged of 0 – 13 weeks, and the other 35 at the aged of 14 – 26 weeks. The data were analyzed by analysis of variance for time of reached the inflection point and the adult size, and by the regression analysis of the sigmoid pattern were used two parameters for newly hatched and reaching the maximum size. The results showed that the inflection point of metatarsus,  tibia fibula, metacarpal, 1 st digiti, 2 nd digiti  3 rd digiti, and  4 th digiti  length is less than a week, the length of  humerus and femur  were achieved at the age of one to two weeks, and the  metatarsal length were reached at the age of two to three weeks. The adult size of locomotor female bali ducks, starting from the length of the femur, followed by the radius ulna, humerus, tibia fibula, 4 th digiti, 3 rd digiti, 2 nd digiti, metacarpal, 1 st digiti and the last one is metatarsus.